Impact of municipal solid waste ash and some nitrogenous fertilizers on wheat plant: growth and nutrients concentration - Saud S. AI-Oud (Universiti Sains Malaysia, 2015)
A pot experiments were initiated to study the effect of Municipal Solid Waste (MSW) ash on dry matter yield and nutrient concentration of wheat, with the aim of determination the rate of ash that could be applied to soils without adversely affecting plant growth. Application of ash at a rate of 0.5% resulted in slight increase in dry matter yield of wheat. Dry matter yield were deceased significantly with addition of 1.5 up to 2.5%, whereas application of 1% ash did not decrease dry weigh. Plant analysis data indicate that addition of MSW ash increased P content significantly, while micro-and heavy metals did not increased to toxic levels. The data suggest that the ash of MSW under study could be applied to soils at a rate of 0.5% without adversely affecting crop growth. Further increases in the rate of added ash could be harmful to crop growth.